Attitude; Physics Learning Concentration - Tari Okta Puspitasari; Nirmala Sari; Yolanda Eka Putri; Nurdatul Jannah (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of this study was to determine the relationship of attitudes to the concentration of student learning in physics at SMAN 10 Batang Hari. The sample used in this study was 121 with the data analysis technique used was purposive sampling. The instrument used was a questionnaire. The statistics used are descriptive statistics and inferential statistics. Where descriptive statistics display the mean, median, and mode. While inferential statistics use a correlation test. The results of this study are the relationship between attitudes to the concentration of learning in physics at SMAN 10 Batang Hari which is indicated by the sig size is 0.05.